Dynamic hydrogen-bonding enables high-performance and mechanically robust organic solar cells processed with non-halogenated solvent - He, Haozhe; Li, Xiaojun; Zhang, Jingyuan; Chen, Zekun; Gong, Yufei; Zhuo, Hongmei; Wu, Xiangxi; Li, Yuechen; Wang, Shijie; Bi, Zhaozhao; Song, Bohao; Zhou, Kangkang; et al. (Nature communications, 2025)
Developing active-layer systems with both high performance and mechanical robustness is a crucial step towards achieving future commercialization of flexible and stretchable organic solar cells (OSCs). Herein, we design and synthesize a series of acceptors BTA-C6, BTA-E3, BTA-E6, and BTA-E9, featuring the side chains of hexyl, and 3, 6, and 9 carbon-chain with ethyl ester end groups respectively. Benefiting from suitable phase separation and vertical phase distribution, the PM6:BTA-E3-based OSCs processed by o -xylene exhibit lower energy loss and improved charge transport characteristic and achieve a power conversion efficiency of 19.92% (certified 19.57%), which stands as the highest recorded value in binary OSCs processed by green solvents. Moreover, due to the additional hydrogen-bonding provided by ethyl ester side chain, the PM6:BTA-E3-based active-layer systems achieve enhanced stretchability and thermal stability. Our work reveals the significance of dynamic hydrogen-bonding in improving the photovoltaic performance, mechanical robustness, and morphological stability of OSCs. Developing high-performance and mechanically robust active-layer systems is crucial to commercializing flexible organic solar cells. Here, authors design small molecule acceptors with ethyl ester side chains and achieve certified efficiency of over 19% for mechanically robust devices.